2018
DOI: 10.1049/iet-map.2017.0860
|View full text |Cite
|
Sign up to set email alerts
|

Compact dual‐band monopole antenna with defected ground plane for Internet of things

Abstract: Internet of things (IoT) is a complex network of physical objects capable of wirelessly communicating with each other. For implementing such an enormous network, the authors design a compact dual‐band antenna with simple structure. By folding the radiating element and resetting the ground plane, the whole size of the designed antenna is only 14 mm × 14 mm same as a thumbnail, which makes the designed antenna easy to fabricate. The fabricated antenna can operate (return loss S11<−10 dB) at two operating bands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…At the three resonant frequencies, the length of the responsible part for each resonance is calculated by Ref. . The guided wavelengths and corresponding resonant frequencies are related by Equation . λg=cfεr+12 …”
Section: Design Geometry and Analysismentioning
confidence: 99%
“…At the three resonant frequencies, the length of the responsible part for each resonance is calculated by Ref. . The guided wavelengths and corresponding resonant frequencies are related by Equation . λg=cfεr+12 …”
Section: Design Geometry and Analysismentioning
confidence: 99%
“…Researchers around the world have worked on design, fabrication, and optimization of antennas for FSS and DBS according to ITU norms. In [11], a dual-band antenna with 3.4-3.6 GHz and 5.725-5.825 GHz for 5G and 5.8G Wi-Fi are achieved, respectively. A Spidron-Fractal antenna operating in the Ku band of 11.44-12.48 GHz and 13.47-14.39 GHz is proposed by Nguyen Thi et al in [12].…”
Section: Introductionmentioning
confidence: 99%
“…Mishra et al 14 presented high gain Metamaterial based miniaturized antenna using electric LC resonator. Mao et al 15 suggested a dual-band antenna by folding the radiator along with defected ground structure (DGS) for Wi-Fi applications. In References 16-19, miniaturization of patch and its array elements achieved using DGS.…”
Section: Introductionmentioning
confidence: 99%